EcoBin / Nadia Nadhira Rosli - Rosli, Nadia Nadhira (2020)
The EcoBin is a mini automatic separator machine for household which offer a better way to separate between the recyclable and non-recyclable items. This product focuses on using the infrared technology together with the coding programmed written by the programmer. The targeted customer for this product is the housewives and also those who concern about the rule and regulation set by the SWM Environment Sdn Bhd. The rule is the waste product must be separated from home before the concession company collect the waste product from houses.There are some competitive advantages which are smart trash bin that separate the waste product using the AI, trash bin that is equipped with motion sensor lid and trash bin that features advanced infrared technology. These advantages from the competitors have made our company to be aware and ready to face the risk. Based on their advantages and disadvantages, we can improve our product to be more reliable and acceptable by the customers.Our company gain the profit from the sales after calculating the total of production cost, advertisement cost, employee salaries and the utility bills. Our company’s management team consist of the general manager, production manager, marketing and sales manager, finance manager, quality control manager and human resources manager.